Risk Factors Predicting Juvenile Recidivism - Erbay, Ayhan; Gülüm, Zeynep (The Bulletin of Legal Medicine, 2018)
Objective: The identification of risk factors for juvenile recidivism is crucial to prevent recurrent juvenile delinquency. The aim of the present study is to determine the variables that predict juvenile recidivism. In this regard, it is aimed to reveal predictive factors of juvenile recidivism by comparing one-time offenders with three and more time offenders. Materials and Methods: In order to determine the factors that predict juvenile recidivism, data set derived through a retrospective analysis of social inquiry reports from Istanbul Child Court and Istanbul Child Criminal Court where adjudication held between 2005-2015. Social Inquiry Reports about at least three-time offenders (n=200) and one-time offenders (n=200) were examined. Data were classified into the main risk factors. Logistic regression analysis was used to determine risk factors that predict juvenile recidivism. Results: It is found that risky peer groups, spend time in internet cafe, school dropout have most significant prediction on juvenile recidivism. In addition, it is also found that number of siblings, age in the first delinquent behavior, weakness of familial sharing and communication and drug abuse have significant effect on juvenile recidivism. Conclusion: It is understood that juveniles who are between the age of 12-15, being one-time offender, having risky peer group, spending most of the time in internet cafe, and dropped out of the school most likely turned into recidivist. It is important for the protection of the child, as well as for the community, that the family, community and authorities should take the necessary precautions to ensure that the...